The "final solution" in Riga : exploitation and annihilation, 1941 - 1944 - Angrick, Andrej 1962- (Studies on war and genocide, 2009)
Latvia caught between two dictatorships -- Operation Barbarossa : preparations for the German attack on the Soviet Union -- From the pogroms to the establishment of the ghetto -- Securing German rule in occupied Riga : the period of the large ghetto for Latvian Jews -- Murder on a massive scale : the murder of the ghetto's Latvian Jews -- In search of territories for the "final solution" : the road to Riga as a final destination for deportations -- Plans for the Salaspils Camp -- The deportation of German Jews to Riga -- The Salaspils Camp : a detention center with many functions -- German Jews build Salaspils : December 1941-August 1942 -- Excursus 1. SS Major Rudolf Lange and the Wannsee Conference -- The Latvian labor market and the compulsory deployment of Jews in Riga -- The utilization of Jewish assets and the issue of ghetto administration -- Ghetto life and forced labor in Riga in spring 1942 -- The turning point : Operation Dünamünde at Jungfernhof and in the "ghetto for Reich Jews" -- Forced labor and annihilation in County Commissariat Riga City -- Failed resistance : the Tin Square Operation, October 1942 -- Annihilation instead of forced labor: Himmler's struggle against production constraints and armaments interests in General Commissariat Latvia -- Concentration Camp Kaiserwald and the barrackings -- Excursus 2. SS Second Lieutenant Fritz Scherwitz, the commander at Lenta : a biographical sketch -- The decommissioning of Concentration Camp Kaiserwald, evacuation, and liberation -- A new start and the search for justice -- Conclusion -- Glossary -- Organizational chart -- Table of ranks -- Biographical appendix